Source book of enzymes - White, John Stephen (CRC Press, 1997)
The Source Book of Enzymes answers these important questions and many more:Where can I find a particular enzyme? What enzymes are available for purchase? How do I select the appropriate enzyme for my pplication?How do the available enzymes differ from one another?What are the reaction conditions for optimum enzyme performance? Who sells the enzyme I need?